Craniocaudal cyclic load improves risk assessment of lumbar pedicle screw loosening: finite element analysis based on computer tomography - Jiang, Chenyu; Ouyang, Hanqiang; Li, Yali; Lang, Ning; Zhang, Yan; Jiang, Liang; Yuan, Huishu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPedicle screw loosening (PSL) is a frequent complication in osteoporotic patients undergoing spinal fixation, yet effective risk assessment methods are limited. This study explores the impact of craniocaudal cyclic load on pedicle screw fixation strength using computed tomography-based finite element analysis (CT-FEA) and evaluates its predictive value for PSL.MethodsA total of 23 PSL cases (7 men and 16 women) and 29 matched controls were analyzed using CT-FEA. Both a simple axial pullout load and a pullout load with a preset craniocaudal cyclic load were applied to calculate the pullout force. Hounsfield unit (HU) values and volumetric bone mineral density (vBMD) of the screw trajectory were also assessed for osteoporosis evaluation. The pullout force and osteoporotic assessment value were compared between PSL and controls.ResultsCraniocaudal cyclic loading significantly reduced the pullout force (924.3 ± 195.1 N vs. 745.2 ± 188.7 N, p < 0.0001). The PSL group had a lower pullout force under cyclic load (629.6 ± 188.2 N vs. 836.9 ± 131.6 N, p < 0.0001) and lower HU value of screw trajectories (183.7 ± 42.6 vs. 206.7 ± 29.72, p = 0.026) than controls, while simple axial pullout force and vBMD showed no significant differences. Receiver operating characteristic (ROC) analysis indicated that pullout force under cyclic load (AUC = 0.806) was a better predictor of PSL than HU values (AUC = 0.629).ConclusionThis study demonstrates the critical role of craniocaudal cyclic loading in pedicle screw fixation strength and its predictive value for PSL. Craniocaudal cyclic load reduces screw fixation strength significantly. Pullout force under cyclic load assessed by CT-FEA enhances the predictive accuracy for PSL risk.